New records of Libellula pulchella (Odonata: Libellulidae) and Phyllogomphoides albrighti (Odonata: Gomphidae) from the Cuatro Ciénegas Basin, Coahuila, Mexico - Enrique González Soriano (Revista Mexicana de Biodiversidad)
The first records of Libellula pulchella from México and for Phyllogomphoides albrigthi from Coahuila are reported. These records extend the known geographic range of Libellula pulchellabeyond south of Texas and Phyllogomphoides albrigthi beyond west of Nuevo León. The specimens were collected in the Cuatro Ciénegas Basin, one of the most biologically interesting areas for the study of aquatic insects